Pollution acts as one of the determinants of government pollution abatement expenses in Malaysia: using a simultaneity approach / Halimahton Borhan and Elsadig Musa Ahmed - Borhan, Halimahton; Musa Ahmed, Elsadig (Division of Research, Industrial Linkages and Alumni, UiTM Cawangan Melaka, 2011)
A major worldwide problem is pollution. It causes death, develops health problems and exasperates existing health problems. Pollution is also creditworthy for a broad kind of environmental problems. All these effects imply substantial economic costs. Pollution abatement turns increasingly significant as these costs get widely acknowledge. The aims of this study are to examine the relationship between economic growth and different indicators of air and water pollution in Malaysia and to investigate the determinants of government pollution abatement expenses using a simultaneous equation method. Air pollution indicators were assessed on a number of measures: Carbon Monoxide (CO), Sulphur Dioxide (SO2), Nitrogen Dioxide (NO,), Ozone (O3), Particulate Matter (PM10) and Suspended Particulate Matter (SPM). Water pollution indicators were assessed on a number of measures: Biochemical oxygen demand (BOD), Cadmium (CD) and Arsenic (AS). The income level per capita, GDP (Gross Domestic Product) per capita were measured from the year 1996 to 2006 quarterly. This study contributes to the available literature by Hung et al (2004) and Shen (2006) by adopting the model and expanding it to include variables such as the number of motor vehicles, foreign direct investment, and government spending, secondary industry share and government pollution abatement expenses. Being different from the study by Hung et al (2004) and Shen (2006), this study estimates population density as an endogenous variable. It formulates a four-equation simultaneous model for empirical research. It is testing for exogeneity using the Hausman test and estimates the simultaneity model using the two-stages least squares method. The EKC hypothesis is supported in the cases of SO, O, CD and BOD. The simultaneity exists for all the indicators of air and water pollutants except for NO2 and AS. There are several differences found between single polynomial equation estimators commonly used in EKC literatures and simultaneous equation estimators. Most of the pollutant indicators showing a highly significant effect on government pollution abatement expenses except for NO, and BOD.